2013
DOI: 10.1007/978-3-642-41248-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Music Emotion Recognition: From Content- to Context-Based Models

Abstract: The striking ability of music to elicit emotions assures its prominent status in human culture and every day life. Music is often enjoyed and sought for its ability to induce or convey emotions, which may manifest in anything from a slight variation in mood, to changes in our physical condition and actions. Consequently, research on how we might associate musical pieces with emotions and, more generally, how music brings about an emotional response is attracting ever increasing attention. First, this paper pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 60 publications
(83 reference statements)
0
45
0
1
Order By: Relevance
“…In the Fig 3. raga cluster formation technique includes the KNN [9] [14]and SOM approach which is the best suited. In the fig.…”
Section: Algorithm Stepsmentioning
confidence: 99%
“…In the Fig 3. raga cluster formation technique includes the KNN [9] [14]and SOM approach which is the best suited. In the fig.…”
Section: Algorithm Stepsmentioning
confidence: 99%
“…In contrast, dimensional models represent music moods with continuous values in a low‐dimensional space. The most adopted dimensional model in MIR is Russell's model (Barthet, Fazekas, & Sandler, ; Kim et al, ; Yang & Chen, ), which consists of two dimensions, valence (measuring the level of pleasure) and arousal (measuring the level of activity) (Russell, ). This study also adopts this model, as reprinted in Figure .…”
Section: Related Workmentioning
confidence: 99%
“…Studies on music mood recognition (MMR) revealed that, for dimensional models, music valence was consistently more difficult to predict than arousal (Barthet, Fazekas, & Sandler, ; Yang & Chen, ). For categorical models, it is also found that performances vary across mood categories and the differences might be related to the valence and arousal values corresponding to the categories (Hu, Choi, & Downie, ).…”
Section: Related Workmentioning
confidence: 99%
“…Their test data consisted of 30 tunes in 3 ragas sung by 4 artists. They use harmonic product spectrum algorithm [6][7][8][9][10][11][12] to extract the pitch. The tonic is manually fed.…”
Section: Scale Matchingmentioning
confidence: 99%
“…The central idea in this approach, which is to model a raaga as HMM, was also used in [9]. The same idea is used in an attempt to automatically generate Hindustani classical music [10], but with less success.…”
Section: Statistical Modeling and Pakad Matchingmentioning
confidence: 99%